Carnavescola: produção de uma sinopse de carnaval e composição de samba enredo: uma proposição ao ensino de História - OLIVEIRA, Alex Costa de (Universidade Federal do Pará, 2023)
The current dissertation aims to discuss a suggestion for an action research proposal for teaching history presented to the professional master's course at ProfHistória-UFPa. This aims to firstly understand the popular cultural manifestations of Brazil, such as: samba and carnival, as pedagogical potentialities to be used in teaching-learning within a classroom (even remote) of basic education. For this, a two-stage research process is proposed. The first aimed at achieving academic goals and the second with didactic-pedagogical purposes. In this sense, what is intended is the dialogical link between the concepts of memory, identity: collective and/or cultural, historical awareness and their symbolic representations in the daily lives of students using these potential tools to teach history through production, construction, of a synopsis of carnival and of a textual-poetic body of samba plot by the students. The methodology will also be developed having as support and approach conceptions used in historiography, such as: History of the Present Time, Local History, Oral History. Through sources: visual, virtual, written, sound and oral. Regarding the didactic-pedagogical proposal, the intention is to take it to the classroom (in this case, we had to resort to remote classes due to the social and historical context imposed by the covi-19 pandemic, between 2020 and 2021) experiences of constructing historical reality through samba and carnival, specifically bringing the student body closer to these social, cultural experiences, and also using the synopses and lyrics of the plot sambas, created by these historical subjects, as a source of reflection to historical consciousness analyzed in teaching practice by the professor-researcher. Finally, bring the importance of this relationship "From the street to the classroom" as the construction of analysis and knowledge for exclusively didactic-pedagogical purposes in a History class.